Alternaria radicina; unveiling the cause, spread, and molecular basis of a novel coriander leaf blight disease in Egypt - Khalid M. Ghoneem; Ehsan M. Rashad; Abdulaziz A. Al-Askar; Yosra A. Helmy; Seham M.A. El-Gamal; Shafik D. Ibrahim; WesamEldin I.A. Saber (Heliyon)
Coriandrum sativum L. faced a new and previously undocumented leaf blight disease for the first time. This disease manifests initially as small, circular, or irregular brown spots on older leaves, which gradually expand and merge into dark brownish blotches over time. This disease's impact is detrimental to plant health and seed quality. Through comprehensive morphological characteristics, and molecular identification (GenBank OL823169), the pathogen was conclusively identified as Alternaria radicina. Further confirmation was obtained by analyzing target sequences for the Alt-a-1 gene (GenBank OR492259). Koch's postulates were strictly adhered to, leading to the successful re-isolation of A. radicina from artificially infected 8-week-old coriander plants (local variety; Balady), providing unequivocal evidence that the fungus is responsible for leaf blight disease, marking the first such confirmation worldwide. The significant activity of fungal enzymes may be associated with pathogenicity. The seed-health test supported the hypothesis that seeds play a central role in the transmission of A. radicina, as it was detected in 40 % of seed lots, alongside other common pathogenic and saprophytic genera. This study underscores the urgency of implementing seed treatments to curtail the pathogen's spread. The emergence of coriander leaf blight disease documented here (Egypt; 30° 57′ 25″ N and 31° 35 ′ 54″E) for the first time, necessitates heightened awareness and proactive measures to protect coriander plants all over the world.